2014
DOI: 10.1038/ki.2013.532
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetics influence the incidence of acute kidney injury following valvular heart surgery

Abstract: Propofol has been shown to provide protection against renal ischemia/reperfusion injury experimentally, but clinical evidence is lacking. Here we studied the effect of propofol anesthesia on the occurrence of acute kidney injury following heart surgery with cardiopulmonary bypass. One hundred and twelve patients who underwent valvular heart surgery were randomized to receive either propofol or sevoflurane anesthesia, both with sufentanil. Using Acute Kidney Injury Network criteria, significantly fewer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 39 publications
5
66
0
1
Order By: Relevance
“…In this matched population, propofol was associated with statistically lower risk for developing AKI and several other important renal-related outcomes. The results of this propensity score analysis, which controlled for important pretreatment variables and for mechanical ventilation dependence, are supported by previous animal studies and one small but important randomized clinical trial in patients undergoing valvular heart surgery (8,10,11).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In this matched population, propofol was associated with statistically lower risk for developing AKI and several other important renal-related outcomes. The results of this propensity score analysis, which controlled for important pretreatment variables and for mechanical ventilation dependence, are supported by previous animal studies and one small but important randomized clinical trial in patients undergoing valvular heart surgery (8,10,11).…”
Section: Discussionmentioning
confidence: 49%
“…Several animal studies suggested that propofol is effective in attenuating AKI in different models (8)(9)(10). Although it is commonly observed that therapeutic and preventive strategies related to AKI are successful in animal models and fail in human trials, a recent randomized controlled study showed that propofol anesthesia was associated with a reduction in AKI incidence in patients undergoing valvular heart surgery compared with sevoflurane anesthesia (11). Although these findings are intriguing, our enthusiasm is limited by the small number of patients involved and conflicting results with similar previous small trials also testing propofol.…”
Section: Introductionmentioning
confidence: 99%
“…Measured perioperative changes in serum biomarkers of renal injury and inflammatory mediators, and the occurrence of postoperative complications contributed to the clinical evaluation of patient outcomes. C-reactive protein, creatine kinase-MB, and neutrophil counts were measured pre- and postoperatively, and interleukin-1, interleukin-6, and tumor necrosis factor-α levels were assessed to evaluate the degree of inflammation and AKI [61]. In another study, patients treated with propofol had better ICU survival than those treated with benzodiazepine.…”
Section: General Anesthesiamentioning
confidence: 99%
“…In a comparison between patients receiving propofol or sevoflurane during cardiopulmonary bypass, propofol significantly reduced the incidence and severity of AKI (which was defined using the AKI network criteria as an absolute increase in serum creatinine of 0.3 mg/dL, an increase ≥150% from the baseline value, or as a urine output of <0.5 mL/kg/h for >6 h within 48 h postoperative) in comparison to sevoflurane [61]. This suggests that propofol may be a better renoprotective agent for cardiopulmonary bypass than sevoflurane.…”
Section: General Anesthesiamentioning
confidence: 99%
“…In parallel with the increase in the number of studies demonstrating the protective role of sevofl urane against the occurrence of AKI, there is also a large number of studies on the protective eff ects of other anesthetics, such as propofol, with regard to AKI. While some studies point to a stronger protective effect of propofol as compared with sevofl urane relative to the occurrence of AKI 24 , others demonstrated that there were no statistically signifi cant diff erences in the incidence of AKI between the two groups 25,26 .…”
Section: Modulation Of Ischemia/reperfusion Injury and Anti-infl Ammamentioning
confidence: 99%